ANALISIS SHARIAH COMPLIANCE PENETAPAN HARGA LELANG BARANG JAMINAN DALAM MENGURANGI RISIKO PADA PEMBIAYAAN IB GRIYA DI BANK SUMUT SYARIAH CABANG MEDAN - Winda Sari Panjaitan; Muhammad Arif; Muhammad Lathief Ilhamy (el-Amwal, 2022)
This research was conducted to determine shariah compliance in determining the auction price of collateral for ib griya financing at Bank Sumut Syariah Medan Branch. The research method used in thisresearch is a descriptive method, in which data are collected, compiled, grouped and analyzed based on facts obtained from the field and then integrated into a clear and focused picture of the problem being studied. While the types of data needed are primary data in the form of interviews with internal bank parties and secondary data in the form of libraries, brochures, articles, and websites. From the results of this study, the authors conclude that 1) the implementation of the mechanism for pricing in the auction of collateral goods is to set a limit value based on the market value and the determination of the auction price set by the Public Appraisal Service Office (KJPP).After the stages of determining the auction price are completed, the bank will submit an auction application and other requirements to the State Property and Auction Service Office (KPKNL). 2)inthe mechanism of price fixing and auction implementation as seen from Shariah Compliance (according to Islamic Sharia) is in appropriate to sharia rules and applicable legal rules, because each step by step the pricing mechanism and auction implementation look at the base price of the auction first bysurveyingto the local market and the central market, a re-assessment carried out by experts in their respective fields, following the rules of procedure, and using the valid data so that it can be facilitated and it does not cause loss to both parties. Therefore it can be concluded that the determination of the auction price for collateral goods in Reducing Risk in Ib Griya Financing at Bank Sumut Syariah Medan Branch is in accordance with shariah compliance (sharia provisions).